Reducing Stigma Toward Mothers in Stunting Incidence by Increasing Fathers’ Participation in Raising Children - Prianto, Budhy; Molyo, Priyo Dari; Widayati, Sri; Setiyaningsih, Lian Agustina; Nuswantari, Sekar Arum (Journal of Population and Social Studies [JPSS], 2024)
Stunting has been considered a global problem that requires considerable attention and action to eradicate, including in developing countries like Indonesia. Initiatives have been made to reduce stunting in many parts of the country, yet they do not seem to bring the expected results. As such, we conducted a study to improve the situation by reducing stigma towards mothers and increasing fathers’ participation in caring for their children. The study was a case study. Data were collected through in-depth interviews and focus group discussions (FGD) with families of stunted children. The study’s novelty lies in the proposed policy model of reducing stigma towards mothers and increasing fathers’ participation in child-raising to reduce stunting. Our findings confirm that mothers must be dealing with a stereotype of ideal mothers, and they find it hard to gain autonomy in decision-making related to their child’s upbringing, including health. Furthermore, findings also show that fathers’ participation in raising children is one of the solutions to reduce stunting. Fathers’ crucial roles are controlling their child’s nutrition, including feeding patterns, taking the child to health facilities, and keeping vaccination schedules. Reducing stigma toward mothers emphasizes gender-sensitive parenting and support from government agencies responsible for stunting eradication. Meanwhile, heterogeneity in how family members perceive stunting has also become another significant challenge that needs deeper exploration. Finally, this study presents policy recommendations to support fathers’ roles in overcoming stunting.